2007
DOI: 10.2164/jandrol.106.000695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Testosterone on Intracavernous Pressure Elicited With Electrical Stimulation of the Medial Preoptic Area and Cavernous Nerve in Male Rats

Abstract: ABSTRACT:We studied the effects of castration and testosterone (T) replacement on intracavernous pressure (ICP) elicited with electrical stimulation of the medial preoptic area (MPOA) and cavernous nerve (CN) in male rats. We measured the ICP during electrical stimulation of the MPOA and CN in castrated male rats with and without testosterone replacement. The experimental group consisted of 20-week-old male rats at 2 weeks (n 5 8), 4 weeks (n 5 8) and 8 weeks (n 5 8) after castration, and at 8 weeks after cast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
1
26
0
1
Order By: Relevance
“…These alterations included signs of nerve degeneration, and especially myelin sheath degeneration. In a study by Suzuki et al, 9 the same effect of castration was shown to affect cavernous nerves as well. Indeed, in their study, performed on 24 male rats, intracavernosal pressure elicited with electrical stimulation of the cavernous nerve was shown to be significantly lower in castrated male rats compared to the intact controls 0.31 (0.22-0.39) median intracavernosal pressure/blood pressure ratio compared to 0.58 (0.40-0.68) (P,0.01, Mann-Whitney test).…”
Section: Peripheral Action Of Adt On Male Sexual Behaviormentioning
confidence: 86%
See 1 more Smart Citation
“…These alterations included signs of nerve degeneration, and especially myelin sheath degeneration. In a study by Suzuki et al, 9 the same effect of castration was shown to affect cavernous nerves as well. Indeed, in their study, performed on 24 male rats, intracavernosal pressure elicited with electrical stimulation of the cavernous nerve was shown to be significantly lower in castrated male rats compared to the intact controls 0.31 (0.22-0.39) median intracavernosal pressure/blood pressure ratio compared to 0.58 (0.40-0.68) (P,0.01, Mann-Whitney test).…”
Section: Peripheral Action Of Adt On Male Sexual Behaviormentioning
confidence: 86%
“…In a study by Yeh et al,8 administration of Gingko Biloba extract (EGb 761) to male rats increased the number of intromissions and was associated with higher levels of dopamine in the MPOA, but had no effect on the number of mounts, mount latency, intromission latency, ejaculation latency or post-ejaculatory interval, and seemed to be related to the activity of not all but a subregion of MPOA. In another study by Suzuki et al, 9 including 24 castrated male rats, erectile responses elicited by electrical stimulation of the MPOA were eliminated following castration, but restored after testosterone replacement. This illustrates the crucial role of testosterone in the central pathways that oversee sexual function.…”
Section: Central Actions Of Adt On Male Sexual Behaviormentioning
confidence: 91%
“…These structural alterations may be responsible in part for the marked reduction in the intracavernosal pressure (attenuated blood flow) observed in the experimental animals [11]. In addition, recent studies have demonstrated that penile erection in rats, elicited by stimulation of the medial preoptic area, is testosteronedependent [12]. Thus, testosterone may regulate central mechanisms of penile erection, as well as peripheral neural mechanisms.…”
Section: Testosterone Regulates Nerve Structure and Functionmentioning
confidence: 99%
“…Ook kan testosteron de initiatie van de erectie beïn-vloeden door de secretie van de hersenneurotransmitters te veranderen, zoals dopamine, oxytocine of NO van de mediale preoptische area [39]. Dierexperimenteel onderzoek laat zien dat circulerende androgenen neuroprotectief zijn en noodzakelijk voor zenuwregeneratie na een laesie [40].…”
Section: Testosteron En Edunclassified